2015
DOI: 10.1016/j.bbmt.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

HLA-Haploidentical Peripheral Blood Stem Cell Transplantation with Post-Transplant Cyclophosphamide after Busulfan-Containing Reduced-Intensity Conditioning

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-SCT) using post-transplant cyclophosphamide (PTCy) is increasingly performed. We conducted a multicenter phase II study to evaluate the safety and efficacy of PTCy-based HLA-haploidentical peripheral blood stem cell transplantation (PTCy-haploPBSCT) after busulfan-containing reduced-intensity conditioning. Thirty-one patients were enrolled; 61% patients were not in remission and 42% patients had a history of prior allo-SCT. Neutrophil engraftment was ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 38 publications
3
57
2
5
Order By: Relevance
“…In contrast to the rates of GVHD observed in haploidentical HCT recipients receiving PTCy (Luznik et al , ; Bacigalupo et al , ; Ciurea et al , ; Sugita et al , ), we found higher than expected rates of GVHD in our study. The burden of alloreactive T cells is much higher in the major histocompatibility complex (MHC)‐mismatched setting and it is pertinent to assume that a greater degree of mismatch at major HLA antigens will result in a more profound T cell proliferation and more efficient clonal deletion by post‐transplant cyclophosphamide.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the rates of GVHD observed in haploidentical HCT recipients receiving PTCy (Luznik et al , ; Bacigalupo et al , ; Ciurea et al , ; Sugita et al , ), we found higher than expected rates of GVHD in our study. The burden of alloreactive T cells is much higher in the major histocompatibility complex (MHC)‐mismatched setting and it is pertinent to assume that a greater degree of mismatch at major HLA antigens will result in a more profound T cell proliferation and more efficient clonal deletion by post‐transplant cyclophosphamide.…”
Section: Discussioncontrasting
confidence: 99%
“…16 Furthermore, only 26 (20%) of our patients received post-transplant cyclophosphamide (PTCy) as GVHD prophylaxis; use of PTCy has previously been associated with lower rates of GVHD and NRM. 17 Shortcomings of our study include the single-center setting and small sample size, particularly in the NPM1 + /FLT3-ITD − subgroup, which limited our statistical power. Another weakness is related to the fact that we reported FLT3-ITD status dichotomously, as negative or positive, without reference to the actual allelic ratio.…”
Section: Discussionmentioning
confidence: 95%
“…38 Sugita et al 39 recently reported outcomes of 31 patients who received haploidentical PBSC grafts also after RIC conditioning. The NRM in that study was 23%, but this can be partially explained by the rate of graft failure which was 13%, 39 likely due to the inclusion of poor-risk patients including 13 patients who had prior alloBMT. Despite the inclusion of challenging patient population OS, relapse, and disease-free survival rates were 45%, 45%, and 34%, respectively, at 1 year.…”
Section: Expanding the Use Of Ptcy Single-center Experiencesmentioning
confidence: 99%